2021
DOI: 10.3390/vetsci8070124
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis in Domestic Animals: What Our Current Understanding Is and How This Applies to Clinical Practice

Abstract: Atopic dermatitis is a clinical syndrome that affects both people and animals. Dogs closely mimic the complexity of the human skin disease, and much progress has been made in recent years in terms of our understanding of the role of skin impairment and the identification of new treatments. Cats and horses also develop atopic syndromes which include both cutaneous and respiratory signs, yet studies in these species are lagging. It is now recognized that atopic dermatitis is not a single disease but a multifacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 134 publications
0
32
0
1
Order By: Relevance
“…Canine atopic dermatitis (CAD) is an immunoinflammatory cutaneous disease that causes itching (pruritis), swollen spots, and elevated dark gray patches on the paws, neck, ear, mouth, tail, armpit, thighs, and other sites [1,2]. Several owners observed that dogs with CAD start rubbing against objects, scratching, and biting their feet [3].…”
Section: Introductionmentioning
confidence: 99%
“…Canine atopic dermatitis (CAD) is an immunoinflammatory cutaneous disease that causes itching (pruritis), swollen spots, and elevated dark gray patches on the paws, neck, ear, mouth, tail, armpit, thighs, and other sites [1,2]. Several owners observed that dogs with CAD start rubbing against objects, scratching, and biting their feet [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, CAD was considered a histamine-driven type I hypersensitivity triggered by inhalant allergens, with IgE being a key player in the pathogenesis. Nowadays, however, it is seen as a very complex multifactorial syndrome, and it is well established that the skin barrier plays a key role [ 5 , 41 ]. That is why targeting the skin barrier and aiming at restoring it seems like an adequate treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, dogs reflect the complexity of human disease; in fact, in these animals, atopic dermatitis has become more common since the animals have acquired the same lifestyles as the owners, for example increased exposure to clean indoor environments and increased consumption of processed foods. All of these new behaviors have contributed to increasing the risk of developing allergic diseases [ 5 , 6 ]. Given the characteristics of the disease, the impact on quality of life of both dogs and owners is evident, in terms of impact on health, well-being and the human-animal bond [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%